Perspectives of Vocational High School English Teachers Regarding Kurikulum Merdeka - Purwanti, Idah; Wardani, Happy Kusuma (JURNAL PENA EDUKASI, 2024)
Abstract: This article explores the perspectives of English teachers in a vocational high school regarding the implementation of Kurikulum Merdeka. This study investigates various aspects of Kurikulum Merdeka through questionnaires and interviews, including its basic concept, teaching modules, learning processes, and assessment methods. The findings reveal that teachers perceived Kurikulum Merdeka positively. They considered it an improvement over the previous curriculum. Moreover, teachers appreciated the flexibility of Kurikulum Merdeka, although they also emphasized the importance of adequate training and collaboration among teachers for successful implementation. Regarding the learning process, teachers recognized the potential of Kurikulum Merdeka to foster student creativity and social responsibility, mainly through integrating the Pancasila Student Profile Enhancement Project (P5). In terms of assessment, teachers emphasized the importance of diagnostic, formative, and summative assessments in providing continuous feedback. This study provides valuable insights into English teachers' perceptions of Kurikulum Merdeka regarding educational practice in Indonesia's vocational high schools.Keywords: English teachers’ perspectives; Kurikulum Merdeka; vocational high school.